2008
DOI: 10.1007/s00421-008-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyographic responses in quadriceps muscles during fatigue by continuous cycle exercise

Abstract: The present study examined whether the mechanomyogram (MMG) could assess the fatigue-related changes in muscle mechanical properties during cycle exercise. In eight male subjects, the MMG signals were measured in vastus lateralis and rectus femoris by electret condenser microphones. It was found that the integrated MMG (iMMG) showed non linear increase against workload during continuous, incremental cycle exercise and the onset of abrupt changes in iMMG coincided with the ventilatory threshold (VT). Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(43 reference statements)
0
24
0
Order By: Relevance
“…Eleven studies over twenty used an ACC to detect MMG signal [2,[16][17][18][89][90][91][92][93][94], seven used a PIZ [82,[95][96][97][98][99][100], and two utilized an MIC [101,102].…”
Section: Mmg and Fatiguementioning
confidence: 99%
“…Eleven studies over twenty used an ACC to detect MMG signal [2,[16][17][18][89][90][91][92][93][94], seven used a PIZ [82,[95][96][97][98][99][100], and two utilized an MIC [101,102].…”
Section: Mmg and Fatiguementioning
confidence: 99%
“…8,9,32,33 For example, Malek and colleagues 9 reported that the patterns of responses for the normalized MMG amplitude were linear (R ¼ 0.933-0.995) for the vastus lateralis and rectus femoris muscles for all subjects (8 of 8) performing a two-legged knee-extensor exercise, but linear (4 of 8), quadratic (3 of 8), or cubic (1 of 8) for those same subjects performing cycle ergometry. Although Kimura et al 34 reported that the MMG amplitude vs. power output was curvilinear during incremental cycle ergometry for the vastus lateralis and rectus femoris muscles, they did not use polynomial regression but instead described the patterns of responses based on the graphical representation of time vs. MMG amplitude. More recently, however, Zuniga et al 18 reported that the MMG amplitude vs. power output relationship differed within each subject (%27% of all subjects) for the proximal and distal sites on the vastus lateralis muscle.…”
Section: Mmg Amplitudementioning
confidence: 97%
“…Furthermore, MMG MF is associated with muscle fatigue [4, [26][27][28]. It is known that muscle fatigue decreases the MMG MF [26,27]. When the accelerometer mass increases, the reduction in MMG MF can be incorrectly perceived as muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, the natural frequency is inversely proportional to the mass of the spring. Furthermore, MMG MF is associated with muscle fatigue [4, [26][27][28]. It is known that muscle fatigue decreases the MMG MF [26,27].…”
Section: Discussionmentioning
confidence: 99%